The Impact of Analogical Learning and the Feynman Technique on English Achievement and Reasoning Ability in Grade Six : An Experimental Study - Aihua Cheng; Nirat Jantharajit; Supawadee Kanjanakate (JET (Journal of English Teaching), 2026)
Improving both academic achievement and reasoning ability remains a challenge in primary English education. This study examined the effects of integrating analogical learning with the Feynman Technique on Grade 6 students’ English academic achievement and reasoning ability. A quasi-experimental pretest–posttest control-group design was adopted, with two intact classes selected through cluster sampling and assigned to an experimental group (n = 29) and a control group (n = 27); data were collected using an English achievement test and a reasoning ability questionnaire and analyzed using descriptive statistics and t-tests. Results showed that the experimental group significantly outperformed the control group in academic achievement, with posttest scores (M = 85.00, SD = 9.12) exceeding both their pretest scores (M = 80.31, SD = 9.72) and those of the control group (M = 79.96, SD = 9.56). Similar gains were observed in reasoning ability, as the experimental group’s posttest scores (M = 70.55, SD = 9.07) were higher than their pretest scores (M = 65.38, SD = 9.80) and the control group’s scores (M = 65.37, SD = 9.20), suggesting that this integrated approach effectively enhances learning outcomes in primary school English classrooms.